2022
DOI: 10.1007/s10579-022-09589-1
|View full text |Cite
|
Sign up to set email alerts
|

Machine translation in society: insights from UK users

Abstract: Machine translation (MT) tools like Google Translate can overcome language barriers and increase access to information. These tools also carry risks, and their societal role remains understudied. This article investigates typical uses and perceptions of MT based on a survey of 1200 United Kingdom residents who were representative of the national population in terms of age, sex, and ethnicity. We highlight three main findings from our analysis. First, participants often used MT for non-essential purposes that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…These factors alone may present more opportunities for privacy concerns to arise in relation to MT tools, though we note that smartphones are not necessarily the most popular MT use device. Our survey in fact suggests that MT is still mostly accessed on laptops and desktops (Vieira et al 2022; see also Table 1).…”
Section: Survey Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…These factors alone may present more opportunities for privacy concerns to arise in relation to MT tools, though we note that smartphones are not necessarily the most popular MT use device. Our survey in fact suggests that MT is still mostly accessed on laptops and desktops (Vieira et al 2022; see also Table 1).…”
Section: Survey Methodsmentioning
confidence: 86%
“…We outline the methods pertaining to these two data sources below in Sections 3.1 and 3.2, respectively. Further analysis of the UK survey is provided by Vieira et al (2022), and a link to the survey dataset is available at the end of this article (see Data Availability Statement).…”
Section: Methodsmentioning
confidence: 99%
“…This is not an uncommon assumption. In their study, Vieira et al (2022) found that UK-based general users of MT seemed to trust the systems and were satisfied overall with the quality, even though they would ask for better quality when given the chance.…”
Section: Mt For Assimilation and Accessing Informationmentioning
confidence: 99%
“…In 2016, Google Translate was estimated to generate more than 100 billion words per day (Pichai, 2016), and its use has further increased ever since (Pitman, 2021). MT is integrated into e-commerce platforms such as eBay, search engines, and Bahdanau online chats, whereas online MT tools are deployed for a range of use cases by millions of people daily, e.g., for leisure, traveling, or work-related activities (Vieira et al, 2022).…”
Section: Introductionmentioning
confidence: 99%